A Case of Trousseau's Syndrome Accompanying Ovarian Cancer with Widespread Thromboembolisms - Hiroharu Kobayashi; Yoshifumi Arai; Kentaro Iga; Misa Kobayashi; Takashi Suzuki; Satoru Nakayama; Hiroshi Adachi (Hindawi Limited, 2020)
The patient was a 41-year-old woman, gravida 0. She had no notable medical history. Laparoscopic right salpingo-oophorectomy and left cystectomy were performed for bilateral ovarian endometriomas, which were both pathologically diagnosed as benign. Six months later, she presented with left lower abdominal pain and expressive aphasia. Examination revealed multiple cerebral infarctions and pulmonary embolism. The patient was diagnosed with Trousseau's syndrome secondary to ovarian cancer, and anticoagulant therapy was initiated. Despite treatment, she developed visual field loss due to occlusion of the left retinal artery; dizziness due to cerebellar infarction and myocardial infarction; and right hemiplegia due to new cerebral infarction. She received chemotherapy (two courses of paclitaxel and carboplatin), which did not improve her condition, and died two months after onset. An autopsy revealed that her left ovary was enlarged to a size of 12 cm and an endometrioid carcinoma G2 was identified. Ovarian cancer had spread throughout the abdominal cavity, and a large amount of pleural and ascites fluid was present. Multiple thrombi were found in bilateral pulmonary arteries and bilateral common iliac veins. There was a 2.5 cm thrombus in the left ventricle apex, and the anterior descending branch was obstructed by thrombus with recanalization.